2017
DOI: 10.1200/jco.2016.68.1494
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Interim [18F]Fluorodeoxyglucose–Positron Emission Tomography in Advanced-Stage Hodgkin Lymphoma Is Not Well Established

Abstract: 1 that included 331 patients with stage III or IV Hodgkin lymphoma (HL) who underwent interim [18 F]fluorodeoxyglucose (FDG) -positron emission tomography (PET) after two cycles (PET2) of ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine). PET2-negative patients received four additional cycles of ABVD, whereas PET2-positive patients were switched to escalated BEA-COPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone) for six cycles. Importantly, no contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…However, we strongly disagree with their conclusions. First, we believe there is no place for interim FDG-PET in routine clinical care, because the results on its value are too heterogeneous [9]. Note that a recently published, prospective large-scale study including 1100 patients with advanced-stage Hodgkin lymphoma reported interim FDG-PET to have no value at all in predicting prognosis [10].…”
Section: Letter To the Editormentioning
confidence: 99%
“…However, we strongly disagree with their conclusions. First, we believe there is no place for interim FDG-PET in routine clinical care, because the results on its value are too heterogeneous [9]. Note that a recently published, prospective large-scale study including 1100 patients with advanced-stage Hodgkin lymphoma reported interim FDG-PET to have no value at all in predicting prognosis [10].…”
Section: Letter To the Editormentioning
confidence: 99%
“…Additionally, the results from our experience with the modified biweekly gemcitabine and nab-paclitaxel regimen appear to be similar to the results of the weekly regimen, as shown in more recent studies. 11 …”
Section: Our Study Versus Historic Controlsmentioning
confidence: 99%
“…In addition, comparisons with historical studies that suffered from inadequate methodology and heterogeneous results are futile (21). We individually criticized all 3 of these studies for these issues (27)(28)(29). On the other hand, multiple, recently published, large-scale studies (14,(24)(25)(26) unambiguously showed that (in contrast to the studies by Gallamini et al (12,13)) a high proportion of the large group of patients with negative interim 18 F-FDG PET/CT results develops disease relapse during follow-up and that, therefore, a negative interim 18 F-FDG PET/CT result cannot exclude residual disease.…”
Section: Replymentioning
confidence: 99%